Effect of grain size and amount of zirconia on the physical and mechanical properties and the wear resistance of zirconia-toughened alumina; Ceramics International; Vol. 46, iss. 7 - Zadorozhnaya O. Yu. Olga Yurjevna; Khabas (Habas) T. A. Tamara Andreevna; Tiunova O. V. Olga Vasiljevna; Malykhin S. E. Sergey Evgenjevich (2020, 2020)
Title screen